Introducing Heterogeneous Form Item Sets in Cognitive Ability Tests: The Case of the Problem Test - Tonković Grabovac, Maša; Urch, Dražen; Huić, Aleksandra (2008)
A new general mental ability test is introduced. The lack of specific instructions and variety of item forms make it suitable for measuring the capacity to adapt to new problems, reducing the exercising effect to minimum. The aim of this research was to make a psychometric validation of the Problem Test. The results of 1200 participants were examined in a real employment testing context. Although the test consists of items heterogeneous regarding their form and content, the Cronbach alpha index points to high test reliability (α=0, 87). The issue of compiling heterogeneous instead of homogeneous item forms is discussed.
ENG